Omboh Dilaut or supernatural in the sea the appropriation of magical realism in writing about the Badjaos - Gayangos, Sigrid Marianne P.; Sanchez, Ana Felicia C. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2013)
The Badjaos are a people with unique belief system that is spiritually connected to th sea. The introductory essay explores the cultural identity of the Badjaos and explains how it is almost impossible to write about them using strictly the realist mode. The collection, entitled Omboh Dilaut, attempts to depict the lives of the Badjaos, where natural and supernatural events are almost indistinguishable from each other.
Thesis (B.A. in Creative Writing)
Keywords: Magic realism (Literature); Bajau (Southeast Asian people) -- Philippines